Vocational Higher Education Students’ Perceptions on the Use of Artificial Intelligence Tools in Learning English Communication Skills - Shanty Halim; Nurul Hidjrah Hairuddin (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Artificial intelligence (AI) tools have become increasingly accessible to university students and are changing how English is practiced, revised, and evaluated. This study investigated Civil Engineering students’ perceptions of AI tools for developing English communication skills at Politeknik Negeri Ujung Pandang, Indonesia. A descriptive survey design was employed with 50 students who had experience using at least one AI-supported application for English learning. Data were collected through a 24-item five-point Likert-scale questionnaire and three open-ended questions. The questionnaire examined usage patterns, perceived usefulness, communication improvement, engagement, and concerns regarding responsible use. Descriptive statistics and thematic analysis were used to interpret the responses. The model findings indicate that students held positive perceptions of AI-assisted English learning, with an overall mean score of 4.12. They considered AI useful for expanding technical vocabulary, correcting grammar, generating ideas, receiving immediate feedback, and preparing presentations or workplace-related communication. Students reported that AI reduced anxiety and increased confidence when composing messages and rehearsing English. Nevertheless, participants expressed concerns about inaccurate information, excessive dependence, academic integrity, privacy, and the limited authenticity of AI-based speaking practice. Students therefore preferred AI to function as a supplementary learning partner rather than a replacement for lecturers, classmates, or real communicative experience. The study concludes that AI tools can support English communication development in vocational higher education when their use is guided by pedagogical objectives, verification practices, ethical rules, and activities requiring meaningful human interaction. These findings offer implications for English instruction in civil engineering and other technical polytechnic programs in Indonesia.